The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s12889-016-3339-8
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of stunting in Indonesian children: evidence from a cross-sectional survey indicate a prominent role for the water, sanitation and hygiene sector in stunting reduction

Abstract: BackgroundStunting in early life has considerable human and economic costs. The purpose of the study was to identify factors associated with stunting among children aged 0-23 months in Indonesia to inform the design of appropriate policy and programme responses.MethodsDeterminants of child stunting, including severe stunting, were examined in three districts in Indonesia using data from a cross-sectional survey conducted in 2011. A total of 1366 children were included. The analysis used multiple logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

32
238
6
95

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 309 publications
(371 citation statements)
references
References 28 publications
32
238
6
95
Order By: Relevance
“…In a recent study, purchase of inexpensive drinking water—which was assumed to be untreated—was associated with increased odds of stunting in children 0–59 months in urban slums (UOR 1.32, 95% CI [1.20, 1.45]; Semba et al, ). Additionally, Torlesse, Cronin, Sebayang, and Nandy () analysed a cross‐sectional survey and demonstrated that children 0–23 months living in a household with untreated drinking water had much higher odds of stunting if the household also used an unimproved latrine (AOR 3.47, 95% CI [1.73, 7.28]). Food insecurity was associated with child stunting in one cross‐sectional study, which found lower odds of stunting (AOR 0.70, 95% CI [0.50, 0.99]) in children 0–23 months in households that consumed more than two meals a day (Ramli et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent study, purchase of inexpensive drinking water—which was assumed to be untreated—was associated with increased odds of stunting in children 0–59 months in urban slums (UOR 1.32, 95% CI [1.20, 1.45]; Semba et al, ). Additionally, Torlesse, Cronin, Sebayang, and Nandy () analysed a cross‐sectional survey and demonstrated that children 0–23 months living in a household with untreated drinking water had much higher odds of stunting if the household also used an unimproved latrine (AOR 3.47, 95% CI [1.73, 7.28]). Food insecurity was associated with child stunting in one cross‐sectional study, which found lower odds of stunting (AOR 0.70, 95% CI [0.50, 0.99]) in children 0–23 months in households that consumed more than two meals a day (Ramli et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Semba et al () reported decreased odds of stunting with higher household animal‐source food expenditure in rural children (UOR 0.87, 95% CI [0.82, 0.92]) and urban poor children (UOR 0.78, 95% CI [0.72, 0.85]) and decreased odds of stunting with higher household plant‐source food expenditure in rural children (UOR 0.79, 95% CI [0.74, 0.84]) and urban poor children (UOR 0.86, 95% CI [0.79, 0.94]) 6–59 months. In a recent study, households without age‐appropriate feeding—which includes a minimum acceptable diet of adequate diversity and frequency—were associated with increased odds of stunting in children 0–23 months (UOR 1.39, 95% CI [1.09, 1.77]; Torlesse et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sebuah penelitian menjelaskan bahwa prilaku higiene yang baik yang dilakukan ibu atau pengasuh alita dapat memberikan efek protektif terhadap kejadian stunting [29] .…”
unclassified